Corporate governance, rating of the EU member states guidelines - Psaros, Jim; Solomon, J. F.; Krambia-Kapardis, Maria (My University, 2007)
The paper presents a synthesis and analysis of corporate governance guidelines of the twenty-five European Union member states. The papes focuses on observable and quantitiable aspects of covernance including key aspects pertaining to the conpositionand operation of the board of ditectors, audit committee...
Keywords: International corporate governance; Ranking of Ueropean Codes